THE ROLE AND POWERS OF LOCAL COUNCILS IN THE FIELD OF LOCAL BUDGET MANAGEMENT IN UZBEKISTAN (TSUL LEGAL REPORT, 2026)
This article examines the evolving role of local councils (Kengashes) in Uzbekistan’s budget formation and execution processes within the framework of ongoing decentralization and public financial management reforms. Drawing on the Constitution, the Budget Code, and the Law “On Local State Authority,” it identifies the constitutional and legal foundations of council authority in fiscal governance. The study employs a qualitative legal-document analysis method combined with international assessments. Findings show that recent reforms have significantly enhanced transparency, citizen participation, and local fiscal oversight. The article highlights that while Uzbekistan’s legal architecture provides robust powers for local councils in budget approval and monitoring, practical challenges remain in ensuring effective autonomy, data transparency, and fiscal discipline at subnational levels. Strengthening institutional capacity, ensuring consistent oversight by councils, and aligning with international governance standards are emphasized as prerequisites for sustainable fiscal decentralization. Overall, the research concludes that empowering local councils through legal and procedural reforms can transform them into key drivers of accountable, inclusive, and development-oriented local governance.